Application of total physical response method in the relations with the acquisition of new vocabularly in kids from 2nd grade of Republica de Francia Elementary School in David, Chiriquí, 2011 - Nieto R., Elaidieth H.; Rellan B., Dayden A. (David, Panamá : UDELAS, 2011)
This Thesis is about the Thotal Physical Response Method; it is a method that approaches to teaching a second language based on listening and related with physical actions.
GENERAL INDEX Acknowledgement Dedication General index Chart index Graphic index Appendix index Introduction CHAPTER I. THE RESEARCH PROBLEM CHAPTER 2. THEORETICAL FRAMEWORK 2.1. Description of T.P.R. method 2.1.2. Advantages and disvantages of T.P.R. method 2.1.2.1. Total physical response disadvantage 2.2. Application of T.P.R. method in the classroom 2.2.1. The skill develop in the total physical response 2.2.2. Theory of language 2.2.3. Theory of learning 2.2.4. Principles of total physical response method 2.2.5. The role of material 2.2.6. Types of T.P.R. method 2.3. Characteristics of T.P.R. method 2.3.1. Profile of children learning styles 2.3.2. Characteristics of the first language acquisition 2.4. The teacher role 2.4.1. The syllable of using total physical response method 2.4.1.2. The components of lesson plan 2.4.2. The teaching process of the total physical response method 2.4.3. Techniques used the teacher in total physical response method 2.5. The student role 2.5.1. The activity for the learned 2.5.2. The evaluation 2.6. Benefits of total physical response method 2.7. Myths of total physical response method CHAPTER 3. RESEARCH METHODOLOGY CHAPTER 4. ANALYSIS AND INTERPRETATION OF THE RESULT CHAPTER 5. PRESENTATION OF THE PROPOSAL Conclusion Recommendation Bibliography
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; VOCABULARY -- TESIS DE LICENCIATURA; FACULTY OF SOCIAL AND SPECIAL EDUCATION; DEGREE IN TEACHING ENGLISH; TOTAL PHYSICAL RESPONSE METHOD